Standard deviation : a novel - Heiny, Katherine (Alfred A. Knopf, 2017)
"The celebrated author of Single, Carefree, Mellow, returns with her debut novel--a rueful, funny examination of love, marriage, infidelity, and origami. Divorcing his wife to marry his girlfriend, Audra, is the one impulsive thing Graham Cavanaugh has ever done. Audra is charming and spontaneous and fun, but life with her can be exhausting, constantly interrupted by phone calls, burdened by houseguests, and populated by old men with backpacks full of origami paper. As Graham and Audra struggle to define their marriage and raise a child with Asperger's, they decide to establish a friendship with his first wife, Elspeth. But former spouses are hard to categorize--are they friends, enemies, old flames, or just people who know you really, really well? Graham starts to wonder: How can anyone love two such different women? Did he make the right choice? Is there a right choice? A novel as poignant as it is hilarious, Standard Deviation never deviates from superb"--